Understanding the trend and patterns of teenage pregnancy in Ghana: evidence from the Ghana demographic and health survey from 1993-2014 - John Tetteh; George Ekem-Ferguson; Phaedra Yamson; Elom Yarney; Henrique Quansah; Daniel deGraft-Amoah; Swithin Mustapha Swaray; Emelia Dodoo; Ofosua Acheampong; Emmanuel Kofi Aidoo; Alfred Edwin Yawson (Taylor & Francis Group, 2022)
This study estimated the trend and growth rate of teenage pregnancy (TP) among adolescent women aged 15-19 years and further assessed significant change over time as well as associated factors. Five rounds of the Ghana Demographic Health Survey (GDHS) were used involving 5598 (from 1993 to 2014) adolescents. Relative percentage change was estimated, and Modified Poisson multivariate decomposition analysis was employed to assess the risk of TP between two GDHS study points. Decomposition and Poisson regression analysis were used to quantify change and associated significant factors. All analyses adjusted for GDHS design structure (clustering, weighting, and stratification) using Stata 16.1. The prevalence of TP ranged from 13.8% in 2008 to 21.5% in 1993, showing a downward linear trend. The overall growth rate of TP showed a reduction of 8%, however, the percentage change over the period envisage an increasing linear trend. The combined effect due to endowment significantly decreased the log rate of TP prevalence by approximately 219, and 64 over GDHS study points 1993-2014 and 2008-2014, respectively. Throughout GDHS study periods, increasing age of the household head (HH), and the number of women in HH significantly decreased the risk of TP whereas individual age, marital status, and current use of contraceptives significantly increased the risk. TP declined from 1993 to 2014, however, the percentage change depicts an increasing trend. To ensure universal access to sexual and reproductive health-care services, reducing the high rate of TP is key to achieving Sustainable Development Goals (SDGs) target 3.7.